Preparation method of PEO-based polymer solid electrolyte

By using PEO-based polymer solid electrolyte containing conductive salts and surface modifiers in sodium ion batteries, the problem of low ion conductivity of existing electrolytes is solved, and the efficient, stable and safe operation of the battery is achieved.

CN119601764APending Publication Date: 2025-03-11ZHEJIANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411776250.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The solid electrolytes of existing sodium ion batteries have problems such as low ion conductivity, complex preparation process and high material cost, which limits the performance improvement and practical application of the battery.

Method used

Using PEO-based polymer solid electrolyte containing conductive salts and surface modifiers, the ionic conductivity and interface affinity of the electrolyte are improved by optimizing the selection and concentration of conductive salts and combined with the introduction of surface modifiers.

Benefits of technology

It effectively improves the ionic conductivity of the electrolyte, promotes the efficient charging and discharging process of the battery, improves the cycle stability and safety of the battery, and simplifies the preparation process and reduces the material cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005171529710000053
    Figure BDA0005171529710000053
  • Figure BDA0005171529710000061
    Figure BDA0005171529710000061
Patent Text Reader

Abstract

The invention relates to the field of sodium ion batteries, in particular to a preparation method of a PEO-based polymer solid electrolyte for a sodium ion battery, which comprises the following steps: adding polyethylene glycol into a solvent to obtain a PEO solution, and adding water into conductive salt to prepare a conductive salt aqueous solution; a conductive salt aqueous solution and a surface modifier are added into the PEO solution, stirring and mixing are conducted at the temperature of 50-70 DEG C, and the obtained mixed solution serves as a coating solution; uniformly coating a pre-cleaned substrate with the coating liquid to form a thin film, and then drying the thin film first and then drying the thin film; and finally, separating the film from the substrate to obtain the PEO-based polymer solid electrolyte. The comprehensive performance of the electrolyte can be improved, so that the requirements of efficient, safe and stable operation of the sodium-ion battery are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sodium ion batteries, and in particular to a method for preparing a PEO-based polymer solid electrolyte for sodium ion batteries. Background Art

[0002] Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles and other fields due to their high energy density and long cycle life. However, the scarcity and uneven distribution of lithium resources have led to high costs and limited the application of lithium-ion batteries in large-scale energy storage. Therefore, finding alternatives to lithium ions has become an important issue in the field of energy storage.

[0003] Sodium-ion batteries are considered to be a promising electrochemical energy storage technology to replace lithium-ion batteries because of their abundant sodium resources, low price and wide distribution. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries, and the storage and release of electrical energy are achieved through the embedding and deintercalation of sodium ions. At present, sodium-ion batteries have made certain progress in positive and negative electrode materials, such as layered oxides, polyanionic compounds, carbon-based materials, etc. However, the research on electrolytes is relatively lagging, and the existing electrolytes have safety and stability issues, which limits the performance improvement and practical application of sodium-ion batteries.

[0004] At present, sodium ion batteries mostly use liquid electrolytes, but liquid electrolytes have problems such as easy leakage, flammability and poor thermal stability, which seriously affect the safety and reliability of the battery. Solid electrolytes have become a hot topic of research due to their high safety, no leakage risk and excellent thermal stability. Among them, polyethylene glycol (PEO)-based polymer solid electrolytes are formed by dissolving sodium salt in the PEO matrix. The ethoxy group of PEO can coordinate with sodium ions, thereby realizing the conduction of sodium ions. West et al. (Brit.Poly.J., 1988, 20(3):243) first reported PEO-based polymer solid electrolytes. P(EO) was prepared by solution casting using NaClO4 as the sodium salt. 12 The ionic conductivity of NaClO4 at 60℃ is 3.1×10 -6 S cm -1 Recently, Tang et al. from Fuzhou University (CN202410359390.5) introduced inorganic halide additives into PEO-based electrolytes, and achieved improvements in the rate performance and stability of the corresponding battery system by regulating the bulk aggregation structure and constructing an interfacial stabilization layer.

[0005] In summary, PEO has attracted widespread attention due to its excellent thermal stability and mechanical properties. However, its ionic conductivity is low at room temperature, which makes it difficult to meet the needs of high-efficiency sodium-ion batteries. In order to improve the ionic conductivity of PEO-based polymer solid electrolytes, researchers have adopted a variety of methods, such as doping nanofillers, introducing plasticizers, and designing copolymers. These methods have improved the performance of the electrolyte to a certain extent, but there are still some problems, such as complex preparation process and high material cost. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing a PEO-based polymer solid electrolyte for a sodium ion battery.

[0007] In order to solve the above technical problems, the present invention provides a PEO-based polymer solid electrolyte, which is a PEO-based polymer solid electrolyte containing a conductive salt and a surface modifier.

[0008] The present invention also provides a method for preparing the above-mentioned PEO-based polymer solid electrolyte, comprising the following steps:

[0009] 1) Add 5 g of polyethylene glycol (PEO) to a solvent (organic solvent) and stir for 1.5 to 2.5 hours to obtain a PEO solution;

[0010] 2) Add water to the conductive salt to prepare a conductive salt solution with a concentration of 0.8 to 1.2 mol / L;

[0011] Add 15-20 mL of a conductive salt solution and 1-5 mL of a surface modifier to the PEO solution obtained in step 1), stir and mix at 50-70° C. for 0.5-1.5 hours (preferably at 60° C. for 1 hour), and use the resulting mixed solution as a coating solution;

[0012] The surface modifier is a silane coupling agent;

[0013] 3) The coating liquid is uniformly coated on the pre-cleaned substrate to form a thin film (uniform thin film), and then dried until the solvent and water in the film are evaporated (dried to constant weight, the drying time is about 0.8 to 1.2 hours), and then dried at 60 to 80°C for 10 to 12 hours (forming a solid electrolyte film); finally, the film is separated from the substrate, and the resulting film is a PEO-based polymer solid electrolyte.

[0014] As an improvement to the preparation method of the PEO-based polymer solid electrolyte of the present invention: the molecular weight of the polyethylene glycol (PEO) in step 1) is in the range of 4000 to 6000.

[0015] As a further improvement of the method for preparing the PEO-based polymer solid electrolyte of the present invention: the solvent in step 1) is acetonitrile (ACN) or dimethyl carbonate (DMC).

[0016] Generally speaking, 40 to 70 mL of solvent is used for every 5 g of polyethylene glycol (PEO).

[0017] As a further improvement of the preparation method of the PEO-based polymer solid electrolyte of the present invention:

[0018] The conductive salt is NaTFSI (sodium bis(trifluoromethylsulfonyl)imide, i.e., sodium fluorosulfonyl imide);

[0019] The silane coupling agent is APTES (3-aminopropyltriethoxysilane).

[0020] As a further improvement of the preparation method of the PEO-based polymer solid electrolyte of the present invention, in step 2):

[0021] The conductive salt solution is added to the PEO solution in 3 to 5 times, and the surface modifier is added at the same time as the conductive salt solution is added for the last time.

[0022] Note: The purpose of adding the conductive salt solution in batches is to allow the conductive salt to react evenly with PEO.

[0023] As a further improvement of the preparation method of the PEO-based polymer solid electrolyte of the present invention, in step 3):

[0024] Use a spin coater or a coating rod to evenly coat the coating liquid on the pre-cleaned substrate;

[0025] When a spin coater is used, the speed of the spin coater is set to 1800-2200 rpm and the coating time is 25-35 s (to ensure the formation of a uniform and non-porous film).

[0026] As a further improvement of the preparation method of the PEO-based polymer solid electrolyte of the present invention, in step 3):

[0027] The substrate is a glass substrate or a silicon substrate; according to a conventional method, acetone, isopropanol and deionized water are used to wash the substrate in sequence to obtain a pre-cleaned substrate.

[0028] The method of the present invention is used to prepare a PEO-based polymer solid electrolyte, which has the following technical advantages:

[0029] 1) By optimizing the selection and concentration control of conductive salt (NaTFSI), the ionic conductivity of the electrolyte is effectively improved, promoting the efficient charging and discharging process of the battery.

[0030] 2) Introduce a surface modifier (silane coupling agent) with hydrophilic and polar-philic functional groups to improve the interface affinity and stability between the final electrolyte and the electrode material, thereby enhancing the cycle stability and safety of the battery.

[0031] 3) Organic solvents (acetonitrile or dimethyl carbonate) are used to dissolve PEO, and no harmful substances are involved in the preparation process of the electrolyte, which meets environmental protection requirements.

[0032] In summary, the present invention aims to provide a novel method for preparing a PEO-based polymer solid electrolyte with high ionic conductivity, excellent electrochemical stability and mechanical properties, and to improve the comprehensive performance of the electrolyte by optimizing material selection and preparation process to meet the needs of efficient, safe and stable operation of sodium ion batteries. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0034] Embodiment 1, the preparation method of PEO-based polymer solid electrolyte, carries out the following steps in sequence:

[0035] 1) Select polyethylene glycol (PEO) with a molecular weight of 4000, weigh 5 g of PEO and add it to 50 mL of acetonitrile (ACN), and stir it thoroughly at room temperature for about 2 hours to dissolve PEO to form a uniform solution, thereby obtaining a PEO solution;

[0036] 2) dissolving NaTFSI as a conductive salt in water to prepare a NaTFSI solution with a concentration of 1 M;

[0037] Under stirring conditions, 20 mL of NaTFSI solution was added to the PEO solution obtained in step 1) in 4 times, so the amount added each time was 5 mL; the purpose of adding in batches was to avoid phase separation or excessive local concentration caused by the rapid addition of a large amount of solution, so as to ensure the uniformity of the PEO solution; 1 mL of silane coupling agent (as a surface modifier) ​​was added at the same time as the last addition of NaTFSI solution; then the temperature was raised to 60° C. and the stirring and mixing was continued for 1 hour to ensure that the conductive salt was fully dissolved in the PEO matrix and the surface modifier was evenly dispersed in the PEO matrix, and the obtained mixed solution was used as the coating solution;

[0038] The silane coupling agent is 3-aminopropyltriethoxysilane (APTES);

[0039] 3) Use acetone, isopropanol, and deionized water to rinse the glass substrate or silicon substrate in turn (this is the conventional method), and use a spin coater or a coating rod to evenly coat the coating liquid obtained in step 2) on the pre-cleaned glass substrate or silicon substrate. The speed of the spin coater is set to 2000rpm, and the coating time is 30s to ensure the formation of a uniform and non-porous film. Place the coated substrate in a ventilated environment or on a heating table to allow the solvent (acetonitrile, water) to evaporate slowly until a solid electrolyte film is formed. This process takes about 1 hour. Then place it in an oven at 80°C and dry it for 12 hours to completely solidify the structure of the PEO-based solid electrolyte. Finally, separate the film from the substrate to obtain a PEO-based polymer solid electrolyte (thickness is about 100μm).

[0040] Embodiment 2: With respect to Embodiment 1, the following changes are made:

[0041] Polyethylene glycol (PEO) with a molecular weight of 6000 was selected, and the rest was the same as in Example 1.

[0042] Embodiment 3, compared with embodiment 1, makes the following changes:

[0043] The amount of NaTFSI solution was changed to 15 mL, which was added in 3 times, that is, the amount added each time was still 5 mL; the rest was the same as Example 1.

[0044] Embodiment 4: With respect to Embodiment 1, the following changes are made:

[0045] The amount of silane coupling agent was changed from 1 mL to 2 mL, and the rest was the same as in Example 1.

[0046] Embodiment 5, with respect to embodiment 1, the following changes are made:

[0047] The amount of silane coupling agent was changed from 1 mL to 5 mL; the rest was the same as in Example 1.

[0048] Embodiment 6: With respect to Embodiment 1, the following changes are made:

[0049] The acetonitrile (ACN) was replaced with dimethyl carbonate (DMC), and the amount used remained unchanged, still 50 mL; the rest was the same as in Example 1.

[0050] Comparative Example 1: The following changes were made relative to Example 1:

[0051] Cancel step 2);

[0052] In step 3), the PEO solution obtained in step 1) is evenly coated on a pretreated glass substrate or silicon substrate; the rest is the same as in Example 1.

[0053] Comparative Example 2: The following changes were made relative to Example 1:

[0054] The amount of NaTFSI solution was changed to 5 mL, added at one time; and the use of silane coupling agent was eliminated; the rest was the same as in Example 1.

[0055] Comparative Example 3-1, with respect to Example 1, the following changes were made:

[0056] The NaTFSI was replaced by sodium bis(fluorosulfonyl)imide NaFSI; the concentration and dosage remained unchanged; the rest was the same as in Example 1.

[0057] Comparative Example 3-2, with respect to Example 1, the following changes are made:

[0058] The NaTFSI was replaced with sodium chloride NaCl; the concentration and dosage remained unchanged; the rest was the same as in Example 1.

[0059] Comparative Example 4: The following changes were made relative to Example 1:

[0060] The surface modifier was changed from 3-aminopropyltriethoxysilane (APTES) to dimethyldichlorosilane (DMDCS), and the amount used remained unchanged; the rest was the same as in Example 1.

[0061] Experiment 1, Mechanical property test: The products obtained from all the above embodiments and all the comparative examples were subjected to tensile test using a material testing machine. The samples were stretched at a constant rate (5 mm / min), the stress and strain data were recorded, and the breaking strength of the samples was measured.

[0062] Tensile strength calculation formula:

[0063] Where F is the breaking load and A is the cross-sectional area (5mm 2 ).

[0064] Experiment 2: All the above embodiments and all the comparative examples were used for the preparation of sodium ion batteries. The sodium ion battery assembly setting referred to steps 4 and 5 of Example 1 of the invention CN117174988A "A method for preparing lithium / sodium ion battery materials and their application in lithium / sodium ion batteries", and the electrolyte in step 4 was replaced with a PEO-based polymer solid electrolyte obtained in the above case of the present invention.

[0065] The details are as follows: the electrochemical workstation is set to electrochemical impedance spectroscopy (EIS) mode, the frequency range of EIS measurement is set to 1 Hz to 1 MHz, the amplitude is set to 5 mV, the impedance spectrum data is collected at room temperature, and the resistance value R of the sample is obtained by fitting the Nyquist curve or Bode, etc.

[0066] Ionic conductivity calculation formula:

[0067] Where L is the thickness of the electrolyte membrane (100 μm), R is the resistance of the membrane (obtained from EIS data), and A is the contact area between the cathode / anode and the membrane (cm 2 ).

[0068] Experiment 3, stability test:

[0069] The assembled cell in Experiment 2 was connected to an electrochemical workstation and operated at 0.1 mA / cm 2 The charge and discharge cycle test was carried out 100 times at a current density of , with the charging voltage range set to 0.01 ~ 2.5V, and the discharging voltage range set to 0 ~ 2.0V. The current, voltage, and power data of each cycle were recorded and the capacity retention rate was calculated.

[0070] Capacity retention rate = discharge capacity at the 100th cycle / initial capacity × 100%.

[0071] Table 1 Mechanical properties of different solid electrolyte films and their application effects in sodium ion batteries

[0072]

[0073]

[0074] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. PEO-based polymer solid electrolyte, characterized in that: It is a PEO-based polymer solid electrolyte containing a conductive salt and a surface modifier.

2. A method for preparing a PEO-based polymer solid electrolyte, characterized in that The following steps are involved: 1) Add 5 g of polyethylene glycol to the solvent and stir for 1.5 to 2.5 hours to obtain a PEO solution; 2) Add water to the conductive salt to prepare a conductive salt solution with a concentration of 0.8 to 1.2 mol / L; Add 15-20 mL of a conductive salt solution and 1-5 mL of a surface modifier to the PEO solution obtained in step 1), stir and mix at 50-70° C. for 0.5-1.5 hours, and use the resulting mixed solution as a coating solution; The surface modifier is a silane coupling agent; 3) The coating liquid is uniformly coated on the pre-cleaned substrate to form a thin film, and then dried until the solvent and water in the film are evaporated, and then dried at 60-80°C for 10-12h; finally, the film is separated from the substrate, and the obtained film is a PEO-based polymer solid electrolyte.

3. The method for preparing a PEO-based polymer solid electrolyte according to claim 2, characterized in that: The molecular weight of the polyethylene glycol in step 1) is 4000-6000.

4. The method for preparing a PEO-based polymer solid electrolyte according to claim 3, characterized in that: The solvent in step 1) is acetonitrile or dimethyl carbonate.

5. The method for preparing a PEO-based polymer solid electrolyte according to claim 3 or 4, characterized in that In step 2): The conductive salt is NaTFSI; the silane coupling agent is APTES.

6. The method for preparing a PEO-based polymer solid electrolyte according to claim 5, characterized in that In step 2): The conductive salt solution is added to the PEO solution in 3 to 5 times, and the surface modifier is added at the same time as the conductive salt solution is added for the last time.

7. The method for preparing a PEO-based polymer solid electrolyte according to any one of claims 1 to 6, characterized in that In step 3): Use a spin coater or a coating rod to evenly coat the coating liquid on the pre-cleaned substrate; When a spin coater is used, the rotation speed of the spin coater is set to 1800-2200 rpm, and the coating time is 25-35 s.

8. The method for preparing a PEO-based polymer solid electrolyte according to claim 7, characterized in that In step 3): The substrate is a glass substrate or a silicon substrate; acetone, isopropanol and deionized water are used to wash the substrate in sequence to obtain a pre-cleaned substrate.

Citation Information

Patent Citations

  • Preparation method of lithium / sodium ion battery material and application of lithium / sodium ion battery material in lithium / sodium ion battery

    CN117174988A

  • Preparation process of halide blended PEO-based electrolyte and application of halide blended PEO-based electrolyte in solid-state sodium battery

    CN118231771A

  • Polysiloxane composite electrolyte, application and preparation method thereof

    CN110931850A

  • Functional electrolyte for improving interface stability of all-solid-state lithium battery and preparation method

    CN114744284A

  • Composite solid electrolyte design for flexible lithium battery

    CN115911517A